Problems and Prospects of Catering Services: A Case Study of Sangli City - Yadav, Jyoti Indupratap; Yallatti, Ravasaheb Mayappa (Indian Journal of Marketing, 2012)
The purpose of this paper is to quantify the service satisfaction levels of customers who are using the services of caterers for their functions like wedding, get together, family function, public/corporate meetings, etc. in Sangli city. The main objectives of this study were to identify problems that influence customer satisfaction and determine their relationships with customer satisfaction. The variables included in this research are opinion about caterers and facility/services provided by caterers, food quality and service quality as independent variables and customer satisfaction as the dependent variable. A survey questionnaire was constructed based on items determined by past research. 150 customers of well-known caterers were selected as a sample. Psychometric testing was conducted to determine the reliability and validity of the questionnaire. This investigation can contribute to catering sector research by highlighting factors which determine service and product quality that influences customer satisfaction and helps the caterers for appropriate improvements.